PENDIDIKAN KERAS DI MASA LALU DAN RELEVANSI HUKUMAN FISIK DI SEKOLAH SAAT INI - Rozikin; Iswatiningsih, Daroe (Penerbit Lafadz Jaya, 2025)
The practice of harsh education that once colored the world of Indonesian education in the past was often associated with discipline and success in forming character. However, along with the development of understanding of children's rights and educational psychology, the practice of physical punishment began to be questioned for its relevance. This article aims to review the journey of harsh education in the past and examine the relevance of physical punishment in the context of today's education. By using a descriptive qualitative approach and literature study, it is obtained that physical punishment is no longer in accordance with the principles of modern education that emphasize humanistic character building. Alternative approaches such as the restitution method and logical consequences are more effective in forming students' moral awareness.